Efficacy and safety of TCMs with anti-inflammatory effect in patients with rheumatoid arthritis: A network meta-analysis - Fang, Jinying; Liu, Mingxuan; Huang, Zhenghui; Ma, Yucao; Wang, Yiwen; Zheng, Xiaojia; Lv, Liu; Liu, Chunpin; Li, Wei; Zhu, Zhenghong; Zhu, Huachao; Hu, Jie; et al. (Frontiers in Immunology, 2023)
Background Traditional Chinese medicines (TCMs), such as Tripterygium wilfordii Hook F (TwHF), Glycyrrhiza uralensis, Caulis sinomenii and others have anti-inflammatory effects. They are widely used in China to treat rheumatoid arthritis (RA), but proof of their use as an evidence-based medicine is little. The aim of this network meta-analysis (NMA) was to evaluate the efficacy and safety of TCMs. Methods By searching online databases and using a manual retrieval method, randomized controlled trials (RCTs) that met specific selection criteria were included in the meta-analysis. The search included papers that were published between the establishment of the databases and November 10, 2022. Analyses were performed using Stata software (version 14) and Review Manager (version 5.3). Results 61 papers with 6316 subjects were included in the current NMA. For ACR20, MTX plus SIN therapy (94.30%) may be a significant choice. For ACR50 and ACR70, MTX plus IGU therapy (95.10%, 75.90% respectively) performed better than other therapies. IGU plus SIN therapy (94.80%) may be the most promising way to reduce DAS-28, followed by MTX plus IGU therapy (92.80%) and TwHF plus IGU therapy (83.80%). In the analysis of the incidence of adverse events, MTX plus XF therapy (92.50%) had the least potential, while LEF therapy (22.10%) may cause more adverse events. At the same time, TwHF therapy, KX therapy, XF therapy and ZQFTN therapy were not inferior to MTX therapy. Conclusions TCMs with anti-inflammatory effect were not inferior to MTX therapy in the treatment of RA patients. Combining with TCMs can improve the clinic efficacy and reduce the possibility of adverse events of DMARDs, which may be a promising regimen. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022313569.